Optical sensor platform based on cellulose nanocrystals (CNC) – 4′-(hexyloxy)-4-biphenylcarbonitrile (HOBC) bi-phase nematic liquid crystal composite films - Santos, Moliria V. [UNESP] (2017)
The preparation of composite materials has gained tremendous attention due to the potential synergy of the combined materials. Here we fabricate novel thermal/electrical responsive photonic composite films combining cellulose nanocrystals (CNC) with a low molecular weight nematic liquid crystal (NLC), 4′-(hexyloxy)-4-biphenylcarbonitrile (HOBC). The obtained composite material combines both intense structural coloration of photonic cellulose and thermal and conductive properties of NLC. Scanning electron microscopy (SEM) results confirmed that liquid crystals coated CNC films maintain chiral nematic structure characteristic of CNC film and simultaneously, transversal cross-section scanning electron microscopy images indicated penetration of liquid crystals through the CNC layers. Investigated composite film maintain NLC optical properties being switchable as a function of temperature during heating/cooling cycles. The relationship between the morphology and thermoresponsive in the micro/nanostructured materials was investigated by using transmission optical microscopy (TOM). Conductive response of the composite films was proved by Electrostatic force microscopy (EFM) measurement. Designed thermo- and electro-responsive materials open novel simple pathway of fabrication of CNC-based materials with tunable properties.